Congenitally Corrected Transposition of the Great Arteries: Mid-term Outcomes of Different Surgical Strategies - He, Xiaomin; Shi, Bozhong; Song, Zhiying; Pan, Yanjun; Luo, Kai; Sun, Qi; Zhu, Zhongqun; Xu, Zhiwei; Zheng, Jinghao; Zhang, Zhifang (Frontiers in Pediatrics, 2022)
Background: Optimal management for congenitally corrected transposition of the great arteries (ccTGA) is controversial. We applied different surgical strategies based on individual variations in our single-centered practice over 10 years, aming to describe the mid-term results. Methods: From Jan 2008 to Jun 2021, 90 patients with ccTGA were reviewed, which was grouped by three different surgical strategies: 41 cases with biventricular correction as biventricular group, 11 cases with 1.5 ventricular correction as 1.5 ventricular group and 38 cases with Fontan palliation as univentricular group. The mean age at primary surgery was 41.4 ± 22.7 months. Patients were followed for mortality, complications, reoperation, cardiac function and valve status. Results: The median follow-up period was 5.1 years (range, 1.5–12.5 years). The overall 10-year survival and freedom from reoperation rate was 86.7% and 82.4%, respectively. There were 3 early deaths and 3 mid-term deaths in biventricular group, while 2 early deaths and 1 mid-term deaths were reported in univentricular group. Although 1.5 ventricular group presented no death and the fewest complications, we still found similar mortality (p=0.340) and morbidity (p=0.670) among three groups. The bypass time, aortic-clamp time and ICU stay length were the longest in biventricular group, followed by 1.5 ventricular group (p<0.001). However, in mid-term follow-up, biventricular and 1.5 ventricular groups both showed excellent cardiac function, and obvious improvement of tricuspid regurgitation (p=0.008 and p=0.051, respectively). Fontan palliation provided acceptable mid-term outcomes as well, despite a lower ejection fraction. Conclusion: Satisfactory mid-term outcomes could be achieved for highly selected ccTGA patients using the whole spectrum of surgical techniques. Moreover, 1.5 ventricular correction, as a new emerging technique in recent years, might hold great promise in the future practice.